Characteristics Associated With Delivery of an Infant With Congenital Syphilis and Missed Opportunities for Prevention—California, 2012 to 2014. Issue 7 (July 2018) - Biswas, Hope H.; Chew Ng, Rilene A.; Murray, Erin L.; Chow, Joan M.; Stoltey, Juliet E.; Watt, James P.; Bauer, Heidi M.
Abstract : Background: Congenital syphilis (CS), the transmission of Treponema pallidum from mother to fetus during pregnancy, can cause adverse birth outcomes. In 2012 to 2014, the CS rate in California increased more than 200% from 6.6 to 20.3 cases per 100, 000 live births. Our objectives were to identify characteristics associated with delivering an infant with CS and missed opportunities for prevention among syphilis-infected pregnant women in California. Methods: We linked California Department of Public Health syphilis surveillance records from women aged 15 to 45 years—diagnosed from March 13, 2012, to December 31, 2014—to birth records. We compared characteristics among mothers who delivered an infant with CS (CS mothers) with mothers who delivered an infant without CS (non-CS mothers) by using χ 2 or Fisher exact tests. To visualize gaps in prevention among syphilis-infected pregnant women, we constructed a CS prevention cascade, a figure that shows steps to prevent CS. Results: During the selected period, 2498 women were diagnosed as having syphilis, and 427 (17%) linked to birth records; 164 (38%) were defined as CS mothers and 263 (62%) as non-CS mothers. Mothers with CS were more likely than non-CS mothers to have their first prenatal care visit in the third trimester. High proportions of mothers in both groups reported high-risk sexual behaviors, methamphetamine use, or incarceration (13%–29%). The CS prevention cascade showed decrements of 5% to 11% in prenatal care receipt, testing, and treatment steps; only 62% of potential CS births were prevented. Conclusions: Multifaceted efforts are needed to address gaps in the CS prevention cascade and reduce CS cases in California. Abstract : We identified missed opportunities for congenital syphilis prevention in prenatal care receipt, syphilis testing, and treatment during pregnancy; only 62% of potential congenital syphilis births were prevented.Supplemental digital content is available in the text.